Organizational Capabilities for Mass Market Innovations in the Emerging Economies: Insights from an Automobile Firm in India - Sharmelly, Rifat; Ray, Pradeep (Journal of Comparative International Management, 2015)
Of late, there has been a dramatic shift of world economic power towards less-developed countries, in particular, emerging economies (EEs). The growing influence of EEs is shifting the global competitive landscape, as these new economies are a great source of opportunity, inspiration and innovation. However, companies face the challenge to identify what organizational capabilities are required to serve mass market customers to meet their unique demand and price-performance conditions. In depth empirical studies in this context are largely unexplored in the academic literature. Focusing on the product innovation for India and other EEs with the creation of passenger vehicles from the Indian multinational automaker- Mahindra & Mahindra, our analysis highlights that capabilities to recombine are required to achieve an altered price-performance package. Furthermore, linkage capabilities are required to economize on resources. Also, capability to modularize is required for product performance improvements to serve multiple tiered customers. Using case study design, our study aspires to contribute to the innovation literature on mass markets formulating a set of testable propositions to advance research in this subject.